A new antibacterial diterpene from the roots of Salvia caespitosa - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2001)
From the roots of Saliva caespitosa Montbret and Aucher ex. Bentham a new diterpene 6beta-hydroxyisopimaric acid (1) has been isolated together with four known diterpenes, one new triterpenoid, 3-acetylvergatic acid (2), as well as five known triterpenoids, two steroids and a flavone. The structures of the compounds were established by spectroscopic analyses. The isolated compounds were tested against standard bacterial strains. Only the new diterpene, 6beta-hydroxyisopimaric acid has strong activity (MIC 9 mug/ml) against S. aureus and (MIC 18 mug/ml) against S. epidermidis as well as against B. subtilis (MIC 9 mug/ml).
Keywords: Salvia caespitosa; lamiaceae; terpenoids; 6 beta-hydroxyisopimaric acid; 3-acetylvergatic acid; antibacterial activity; ABIETANE DITERPENOIDS; PINNATA